Public awareness on the concept and usage of My ID in public agencies / Nur Atikah Mat...[et al.] - Mat, Nur Atikah; Matulidi, Nornadia; Ahmad, Jasmine (2010)
In the current growth of information technology, the Malaysian Government is trying to improve the accessibility of public services and information by using ICT to enable the public to access information and services online. Recently the initiatives of using My ID have been proposed by Malaysian government to rise effectively and efficiently in delivery services to enabling the government to become more responsive to the needs of its citizens. User acceptance is vital for further development of any new introduction of using technology such as MY ID as well as which one of the factors can be the effect on the acceptance of MY ID is user’s awareness. The goal of this study is to present a general overview concept of MY ID, the level of user’s knowledge and awareness about the concept and usage of MY ID in public agencies by government will be evaluated. Studies have investigated the perception of concept and using My ID in public services which related to the public trust in technology towards My ID. In order to attain this goal, a survey was conducted among the Shah Alam public to measure their awareness, acceptance and perception of concept and usage on My ID in public agencies. The findings of the study would enable the government to decide on the need for promotional of using MY ID to improve their quality service and at the same time the public can enjoy the delight services during the service process.